PENGARUH KUALITAS PRODUK DAN KUALITAS PELAYANAN TERHADAP KEPUASAN KONSUMEN PAPA RON担 PIZZA BANDUNG - Hairunnisa, - (2009)
The current development of culinary business shows a very rapid improvement in the lash several years, not only in national scale but also international scale. The businessmen in various industry sector are doing their best effort to in crease the company's competitiveness, at least by maintaining their own business power. This is also true for Papa Ron's Pizza, a company operated in franchise sector who sell their main product, pizza. Papa Ron's Pizza is demended to improve the quality of product and service for their customer satisfaction, because if the customer is statisfied with the service then they will coming again repeatedly and it will give benefits to the company it self. The purpose of this research is (1) to identify the product quality provided by Restorant Papa Ron's Pizza Bandung, (2) to identify the service quality provided by Restoran Papa Ron's Pizza Bandung, (3) to identify the customer statisfaction of Restoran Papa Ron's Pizza Bandung, and (4) to identify the influence of product and service quality towards costumer satisfaction of Restoran Papa Ron's Pizza Bandung. The research method used in investiganting these problems is descriptive and verification method . the samples used is 87 respondents, date are collected by questionnaire instrument and the analysis used is double regression analysis with the aid of Software SPSS 14 for Windows. The research's result shows that the product and service quality has a significant effect to the costumer statisfaction. The calculation result using double linier regression analysis obtains the equation of = 1,860+ 0,146 X1 + 0,173 X2 which means that the increase of product quality of 1 unit and the other varaibles are constant, so that the costomer satisfaction at Papa Ron's Pizza Bandung will increase at the rate of 0,146 and every increase of service quality of 1 unit and other variables are constant, so that customer satisfaction at Papa Ron's Pizza Bandung will also increase at the rate of 0,173. Whereas from the determination coefficient point of view indicates yhe influene of 45,4% which means that the contribution effect of product and service quality towards the customer satisfaction at Papa Ron's Pizza Bandung is 45,4% and the 54,6% remaining is the contribution from another factors ignored by the author.